ANALISIS PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PADA PT. TUNAS HONDA MUARA BUNGO - Muhammad Asman; Delila Fitri Harahab; Isman Isman; Amran Amran; Sasqia Alya Syafriyani (FEBI UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to determine the effect of promotion and price on purchasing decisions for Honda motorcycles at PT. Honda Muara Bungo shoots partially and simultaneously. The total population is 1,084 people and the sample is 92 people with the sampling method using purposive sampling. Based on the results of data processing, the results of the multiple linear regression equation are obtained as follows: Y = 8.171 + 0.029X1 + 0.038X2 + e from the t-test shows that the promotion variable with purchasing decisions shows that t count = 9.995 is greater than t table = 1.987 at the significance level 0.05 then the decision is H0 is rejected Ha is accepted, it can be concluded that promotion has a significant effect on purchasing decisions and the price variable with purchasing decisions shows that t count = 10.778 is greater than t table = 1.987 at a significance level of 0.05 then the decision is H0 is rejected Ha is accepted, it can be concluded that price has a significant effect on purchasing decisions. Based on the simultaneous simultaneous test, the F count value is 207.819 and the F table is 3.10. This indicates that the promotion and price variables have a significant effect on the purchase decision variable. Based on the results of R2 = 0.824, this means that the contribution of X1, X2 to Y is 82.4% and the remaining 17.6% can be explained by other factors outside of this study.